The Evaluation of Electronic and Documentary Evidence in the Civil Sphere: Differences and Implications - Bustamante Rúa, Mónica María; Galvis Lugo, Ángel Francisco (Law, State and Telecommunications Review, 2021)
[Purpose] To analyze the process of evaluation of electronic evidence in the civil sphere in Colombian legislation, from the differential point of view of documentary evidence, taking in account the particular technical elements of this means of evidence. [Methodology] This is a critical doctrinal type research, by contrasting the legal norms that regulate the issue of assessment, with the doctrinal trends that explain the process of evidentiary assessment academically, all applied in parallel to the value judgment that must be made by the civil case judge regarding documentary evidence and electronic evidence in order to establish the differences between both means of evidence and more precisely regarding their judicial assessment, to determine the differential implications of a Correct evaluation exercise of the electronic evidence and its repercussion in the judicial decision as the culmination of the jurisdictional activity.[Findings] The process of evidentiary evaluation is of special importance in the judicial process, since it follows the conviction of the judge of the case regarding the facts of the process, from which the rule of trial is structured; Hence, the evaluation of the electronic evidence implies a differential and particularized process in technical terms, which differs from the evaluation of the documentary evidence, in order to correctly bring to the process the representation of the facts contained in electronic media, which entails the urgent need for basic training of the judge in matters of computer evidence, since the rules of sound criticism and the free assessment of evidence as a standard of evidence, must be added with the assessment of technical and methodological aspects of this means of evidence, whose parameters are established in this investigation.